A 54-year-old Man with HIV-Associated Nephropathy - Ni Putu Belinda Wiraanjani; Desak Nyoman Desy Lestari (Greenation Publisher & Yayasan Global Research National, 2026)
HIV-associated nephropathy (HIVAN) is a renal parenchymal disease that occurs in individuals infected with HIV. HIVAN is commonly found in patients with severe immunocompromise, particularly with CD4 counts <200, although it may also occur during primary HIV infection. HIVAN is rarely reported in Asian countries. In this case, we report a patient with progressively worsening renal function due to HIVAN. A 54-year-old man with a history of HIV presented with fatigue, fever, weight loss, diarrhea, and poor adherence to antiretroviral therapy, leading to a diagnosis of HIVAN. This patient presented with fatigue, fever, weight loss, and diarrhea. Urinalysis showed proteinuria, and renal ultrasonography revealed enlarged, echogenic kidneys. Progressive daily increases in BUN and serum creatinine during hospitalization indicated deteriorating renal function. These findings are consistent with HIVAN. HIVAN is a serious renal disease that may occur in individuals with HIV. It is a known cause of chronic kidney disease and end-stage renal disease (ESRD). Renal function screening in HIV patients is essential to prevent progression to ESRD.